EXISTENCE OF SOLUTIONS FOR A SYSTEM OF ELASTIC WAVE EQUATIONS - CORTÉS--VEGA,LUIS A (Universidad Católica del Norte, Departamento de Matemáticas, 2001)
A simple and short proof of the existence of solutions for the direct scattering problem associated with the system of elastic wave equations is shown